UPAYA MENINGKATKAN KUALITAS MINAT BELAJAR SISWA DI SMPN 3 TANJUNG MEDAN - Munawir Pasaribu; Ilham Ade Pratama (Cattleya Darmaya Fortuna, 2022)
Students' perceptions of skills in teaching PKP Students (Professional AbilityDevelopment). This study aims to determine how much interest students in the world of education. The method used is descriptive method, discussion, practice. Students' opinions (90.5%) or students rarely express theresults of their thoughts, so that it has an impact on students who are bored (less interested) to take part in teaching and learning activities.Teachers in teaching activities are required to use the method so that the objectives of learning activities can be achieved to the maximum. In using the descriptive method, it aims to provide opportunities for students who want to express their opinions, so that students are active and look for solutions/answers to the lesson. The discussion method is to help students who do not understand astudent so that other students can provide statements on the problem. So that students can understandeverything they do not know